Théodore Géricault - Athanassoglou-Kallmyer, Nina (London : Phaidon, 2010)
A monograph exploring the life and works of Theodore Gericault (1791-1824), an artist whose life, imagination and legacy enthrall audiences, artists and critics alike. It explores his interest in medical and psychiatric science, and his empathy for the poor and dispossessed. ## ##Introduction : man of his time ## The spectacle of war : beginnings in life and art ## "C'est de l'antique moderne" : Géricault and Italy ## Military martyrs and military rebels : Géricault and the liberal ideal ## The politics of horror : creating the raft of the Medusa ## Of England and the English : The raft of the Medusa in London ## The reason of unreason : portraits of the insane ## The end and after : histories of Géricault.
boek
Keywords: Géricault, Théodore